North-South relations in scientific publications: editorial racism? - Victora, Cesar G; Moreira, Carmen B (Revista de Saúde Pública, 2006)
The aim of the present study was to comment on the possible existence of editorial prejudice among the editors of scientific journals from Northern countries against Southern authors. We highlight that a study using bibliometric methods documented an important imbalance in terms of the international scientific production of health researchers from high-income countries (the "North") and those from low and middle-income countries (the "South"). In a survey of Brazilian researchers, three in every four blamed this imbalance, at least in part, on prejudice among international editors. This is supported by the fact that a very small percentage of editorial board members of international journals come from the South. Although prejudice can explain part of the imbalance, there are also specific measures that may increase the likelihood of a paper from the South being accepted in international journals. These include the need to invest in the quality of the written text, and to show empathy with editors and readers, emphasizing the contribution of the manuscript to the international literature. Finally, we discuss whether research carried out in the South should be published in national or international journals, and suggest that there are at least six dimensions to this choice. These include language and target audience; type of contribution to knowledge; generalizability; citation index; speed of publication; and open access. The rapid growth in the number of Brazilian contributions to the international health literature shows that editorial prejudice, although often present, can be effectively offset by research with solid methodology and good-quality presentation.